Effect of material human immunodeficiency virus status on outcomes of very low birth weight infants at chris Hani Baragwanath academic hospital - Tiam, Mayowa Modinat (My University, 2014)
Background Human immunodeficiency virus (HIV) sero-prevalence rate during pregnancy was 26% in 2009 in Gauteng. HIV exposure is associated with high morbidity and mortality in infants. Few studies have assessed the effect of HIV exposure on morbidity and mortality in very low birth weight (VLBW) infants. Aim To determine the infant characteristics at birth, morbidity during hospital stay and mortality at hospital discharge of VLBW infants according to maternal HIV status. Methods This was a retrospective cross sectional descriptive study. Hospital records of VLBW infants admitted at the Chris Hani Baragwanath Academic Hospital, Division of Neonatology from 1st January 2011 to 30th June 2011 were reviewed. Data were collected in an Excel spread sheet and imported to STATA version 12 for analysis. Results 302 hospital records of VLBW infants admitted from January to June 2011 were retrieved and reviewed. About a third (34.1%) of VLBW infants were born to mothers who were HIV positive. There were more babies who weighed <1000 grams in the HIV-exposed infants compared to HIV-unexposed infants (p-0.001). HIV exposed infants had a smaller head circumference (p-0.003), a shorter body length (p-0.006) and significantly more severe grades of IVH (p <0.001) compared to HIV unexposed infants. The overall mortality rate in VLBW infants was 27%, with HIV exposed infants having a mortality rate of 38.6% compared to 21% in the HIV-negative infants (p-0.002). Multivariate analysis showed that the main predictor of mortality was birth weight (p<0.001). Conclusion Though on univariate analysis maternal HIV status was associated with mortality in VLBW infants, this effect was not found on multivariate analysis. Therefore the final conclusion from this study is that maternal HIV status has no independent effect on outcomes to hospital discharge in VLBW infants. Birth weight was the predictor of survival in VLBW infants.
Keywords: Infant, Extremely Low Birth Weight